Laminate, and application of the same

A laminate with a 4-methyl-1-pentene polymer resin layer and glass layer addresses the limitations of traditional glass and laminates by offering a lighter, more durable, and low-oxygen permeability solution for electronic device substrates and cover glasses.

JP2025006396APending Publication Date: 2025-01-17MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023107169
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing glass materials used in applications like electronic device substrates and cover glasses are heavy and susceptible to physical impact, thermal shock, and have high oxygen permeability, while conventional glass-resin laminates do not meet the demand for lighter weight and improved chemical resistance, scratch resistance, and transparency.

Method used

A laminate comprising a resin layer made of 4-methyl-1-pentene polymer or its copolymers with ethylene or α-olefins, a glass layer, and an adhesive layer, with specific compositional ranges to achieve a lightweight, low oxygen permeability laminate.

Benefits of technology

The laminate provides a lighter, more impact-resistant alternative to glass and conventional laminates with improved chemical resistance, scratch resistance, and reduced oxygen permeability, suitable for electronic devices and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006396000001
    Figure 2025006396000001
Patent Text Reader

Abstract

To provide a laminate that is lighter in weight than glass or a conventional glass-resin laminate, and has a low oxygen permeability.SOLUTION: There are provided a laminate comprising: a resin layer containing a resin having a density of 1.00 g / cm3 or less; a glass layer made of a glass sheet; and an adhesive layer that bonds the resin layer and the glass layer, and an application of the same.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate including a resin layer and a glass layer, and various uses of the laminate. [Background technology]

[0002] 2. Description of the Related Art Glass plates have excellent weather resistance, chemical resistance, scratch resistance and transparency, and therefore are widely used as building materials, window materials, lighting fixtures, optical materials such as lenses, substrates and cover glasses for electronic devices, and the like. However, glass is a brittle material and is vulnerable to physical shock, and has the problem of being easily broken when struck by flying objects, etc. It is also known that glass is easily broken by thermal shock and has a larger mass than resin materials, which will be described later.

[0003] In order to solve these problems, many proposals have been made regarding laminates in which a resin material is laminated on a glass plate. Although resin materials have the advantages of being more resistant to physical impacts and being lighter than glass, they also have the disadvantages of being inferior to glass in chemical resistance, weather resistance, scratch resistance, and transparency. Patent Document 1 listed below discloses a glass resin laminate in which the thickness and spectral transmittance of an adhesive layer that bonds glass and resin are within a specified range in order to prevent yellow coloration caused by the resin material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-12373 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in applications where glass has traditionally been used, particularly in fields such as substrates and cover glass for electronic devices and touch panels, there is a strong demand for even lighter weight materials than before, and there is a growing demand for materials that are even lighter than the glass resin laminate described in Patent Document 1.

[0006] On the other hand, 4-methyl-1-pentene polymers are known as resin materials that are more excellent in chemical resistance, scratch resistance and transparency than conventional resin materials. Therefore, the present inventors considered using a single layer made of a 4-methyl-1-pentene polymer, but found that since the 4-methyl-1-pentene polymer has high oxygen permeability, there is a concern that the electronic components inside the electronic device may be oxidatively damaged.

[0007] The present invention has been completed in order to solve the above problems, and an object of the present invention is to provide a laminate which is lighter in weight and has lower oxygen permeability than glass or conventional glass resin laminates. [Means for solving the problem]

[0008] The present invention relates to, for example, the following [1] to [9]. [1] Density is 1.00g / cm 3 A resin layer containing the following resin: A glass layer made of a glass sheet; an adhesive layer that bonds the resin layer and the glass layer; A laminate comprising:

[0009] [2] Oxygen permeability is 0.1cm 3 / (m 2 The laminate according to [1], wherein the thermal expansion coefficient is less than 1.0 hr.·24 hr.·atm. [3] The laminate according to [1] or [2], wherein the resin comprises at least one selected from the group consisting of a homopolymer of 4-methyl-1-pentene and a copolymer of 4-methyl-1-pentene with ethylene or an α-olefin (excluding 4-methyl-1-pentene).

[0010] [4] the resin comprises a copolymer of 4-methyl-1-pentene and an α-olefin (excluding 4-methyl-1-pentene); The laminate according to [3], wherein the α-olefin is an α-olefin having 3 to 20 carbon atoms.

[0011] [5] the resin comprises a copolymer of 4-methyl-1-pentene and ethylene or an α-olefin (but excluding 4-methyl-1-pentene); The laminate according to [3] or [4], wherein the content of 4-methyl-1-pentene-derived structural units in the resin is 70.0 to 99.0% by mass, and the content of ethylene-derived structural units or the content of α-olefin-derived structural units in the resin is 1.0 to 30.0% by mass (wherein the total of the content of 4-methyl-1-pentene-derived structural units and the content of ethylene-derived structural units or the content of α-olefin-derived structural units is 100.0% by mass).

[0012] [6] The laminate according to any one of [1] to [5], wherein the resin has an MFR (260° C., 5 kg) of 0.1 to 500 g / 10 min. [7] The laminate according to any one of [1] to [6], wherein the glass sheet has a thickness of 300 μm or less.

[0013] [8] The laminate according to any one of [1] to [7], wherein at least one surface of the glass sheet has a surface roughness Ra of 0.4 nm or less. [9] An electronic device comprising the laminate according to any one of [1] to [8]. Effect of the Invention

[0014] According to the present invention, it is possible to provide a laminate which is lighter in weight and has lower oxygen permeability than glass or conventional glass resin laminates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described in further detail. In the present invention, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. Furthermore, when numerical ranges are described in stages, the upper and lower limits of each numerical range can be combined in any manner. Furthermore, in the present invention, the term "sheet" includes a sheet, a film, a thin film, a flat plate, and the like.

[0016] <Laminate> The laminate of the present invention includes a resin layer, a glass layer, and an adhesive layer.

[0017] Resin layer The resin layer of the laminate of the present invention has a density of 1.00 g / cm 3 The layer contains the following resin: The resin contained in the resin layer has a density of 1.00 g / cm 3 There are no particular limitations as long as the resin is one of the following, and polyolefins such as polyethylene, polypropylene, and 4-methyl-1-pentene polymers, ethylene-vinyl acetate copolymers, ethylene-methacrylic acid copolymers, etc. may be used. The resin contained in the resin layer may be one type alone or a mixture of two or more types of resins.

[0018] In particular, from the viewpoints of light weight, mechanical strength, heat resistance, chemical resistance, and optical properties, it is preferred that the resin contained in the resin layer contains at least one selected from the group consisting of homopolymers of 4-methyl-1-pentene and copolymers of 4-methyl-1-pentene and ethylene or α-olefins (excluding 4-methyl-1-pentene, the same applies below) (hereinafter collectively referred to as 4-methyl-1-pentene polymers). When the resin constituting the resin layer of the laminate of the present invention contains a 4-methyl-1-pentene polymer, the laminate has excellent light weight and excellent chemical resistance and scratch resistance, even when at least one of the surface layers of the laminate is a resin layer, which is preferable.

[0019] When the resin contained in the resin layer is a mixture of a 4-methyl-1-pentene polymer and a resin other than a 4-methyl-1-pentene polymer, the content of the 4-methyl-1-pentene polymer in the resin layer is preferably more than 50% by mass, and more preferably 80 to 100% by mass.

[0020] Hereinafter, the 4-methyl-1-pentene polymer will be described, but the 4-methyl-1-pentene polymer according to the present invention is not limited to the following embodiment. The 4-methyl-1-pentene polymer may be one type alone or a mixture of two or more types. The monomers from which the 4-methyl-1-pentene, ethylene, α-olefin, and other structural units described below are derived may be derived from fossil raw materials or biomass.

[0021] The 4-methyl-1-pentene polymer may be a homopolymer of 4-methyl-1-pentene or a copolymer of 4-methyl-1-pentene and ethylene or an α-olefin. From the viewpoint of fluidity and moldability, however, a copolymer of 4-methyl-1-pentene and ethylene or an α-olefin is preferable.

[0022] In the copolymer, the content of the 4-methyl-1-pentene-derived structural unit is preferably 70.0 to 99.0% by mass, and the total content of the ethylene-derived structural unit or the α-olefin-derived structural unit is preferably 1.0 to 30.0% by mass, from the viewpoint of heat resistance. More preferably, the content of the 4-methyl-1-pentene-derived structural unit is 90.0 to 99.0% by mass, and the total content of the ethylene-derived structural unit or the α-olefin-derived structural unit is 1.0 to 10.0% by mass. Even more preferably, the content of the 4-methyl-1-pentene-derived structural unit is 92.5 to 97.5% by mass, and the total content of the ethylene-derived structural unit or the α-olefin-derived structural unit is 2.5 to 7.5% by mass. However, the total content of the 4-methyl-1-pentene-derived structural unit and the ethylene-derived structural unit or the α-olefin-derived structural unit is 100.0% by mass. In addition, the total content of the 4-methyl-1-pentene-derived structural units, the ethylene-derived structural units, and the α-olefin-derived structural units in the copolymer is preferably 90.0 to 100.0 mass%, and more preferably 100.0 mass%.

[0023] The α-olefin is not particularly limited as long as it is other than 4-methyl-1-pentene, and examples thereof include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. The α-olefin can be appropriately selected depending on the intended use and required properties of the composition containing the 4-methyl-1-pentene polymer.

[0024] For example, from the viewpoint of imparting appropriate elastic modulus, softness, and flexibility, the α-olefin is preferably an α-olefin having 3 to 20 carbon atoms, more preferably an α-olefin having 8 to 18 carbon atoms, and even more preferably at least one selected from 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, and 1-octadecene. Particularly preferably, the α-olefin is 1-decene, or 1-hexadecene and 1-octadecene.

[0025] The 4-methyl-1-pentene polymer may have a structural unit other than the structural unit derived from 4-methyl-1-pentene and the structural unit derived from the α-olefin (hereinafter also referred to as "other structural units") within a range that does not impair the effects of the present invention. The content of the other structural units is, for example, 0.0 to 10.0% by mass.

[0026] Examples of monomers that derive other structural units include cyclic olefins, aromatic vinyl compounds, conjugated dienes, non-conjugated polyenes, functional vinyl compounds, hydroxyl-containing olefins, and halogenated olefins. Examples of cyclic olefins, aromatic vinyl compounds, conjugated dienes, non-conjugated polyenes, functional vinyl compounds, hydroxyl-containing olefins, and halogenated olefins include compounds described in paragraphs

[0035] to

[0041] of JP2013-169685A. When the 4-methyl-1-pentene polymer has other structural units, the other structural units may be contained in only one type, or in two or more types.

[0027] The 4-methyl-1-pentene polymer has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 260°C under a load of 5.0 kg of preferably 0.1 to 500 g / 10 min, more preferably 1 to 250 g / 10 min, and further preferably 10 to 150 g / 10 min. The MFR in the above range is preferable in terms of resin fluidity when producing a resin layer containing a 4-methyl-1-pentene polymer. In the present invention, the MFR of the 4-methyl-1-pentene polymer can be adjusted, for example, by making hydrogen coexist in a reactor during the polymerization reaction.

[0028] The 4-methyl-1-pentene polymer according to the present invention may be an unmodified 4-methyl-1-pentene polymer or a graft-modified polymer obtained by graft-modifying a modified or unmodified 4-methyl-1-pentene polymer with a polar monomer, such as maleic acid.

[0029] The method for producing the 4-methyl-1-pentene polymer is not particularly limited, and for example, the methods described in WO 2001 / 027124, WO 2014 / 050817, etc. can be used. In the method for producing the 4-methyl-1-pentene polymer, a conventionally known polymerization catalyst can be used.

[0030] The density of the resin contained in the resin layer (for example, the above-mentioned 4-methyl-1-pentene polymer) is 1.00 g / cm 3 0.90 g / cm or less from the viewpoint of weight reduction and transparency. 3 It is preferable that the concentration is 0.70 to 0.87 g / cm or less. 3 More preferably, the density is 0.80 to 0.85 g / cm 3 It is particularly preferred that:

[0031] The resin layer may be formed only from a resin, but may also be formed from a resin composition containing a resin as a main component and additives, etc., and the additives can impart desired performance to the laminate. Examples of additives that may be contained in the resin composition forming the resin layer include impact strength modifiers such as elastomers such as olefin-based elastomers; inorganic fillers such as talc, calcium carbonate, metal powder, titanium oxide, and zinc oxide; colorants such as pigments and dyes; antioxidants, ultraviolet absorbers, light stabilizers, heat stabilizers, antistatic agents, crystal nucleating agents, dispersants, flame retardants, flame retardant assistants, and plasticizers. The content ratio of additives in the resin composition forming the resin layer is not particularly limited, but is, for example, 0.01 to 30% by mass. When the laminate is used for applications in which excellent transparency is desired, the total amount of additives in the resin composition forming the resin layer is preferably 1% by mass or less, more preferably 0.5% by mass or less.

[0032] The thickness of the resin layer in the laminate is not particularly limited and can be appropriately set and selected depending on the thickness of the glass sheet to be used and the thickness of the intended laminate, but from the viewpoint of the balance between weight reduction and strength of the laminate, it can be, for example, 300 μm or more and 5.0 mm or less.

[0033] The resin layer may be molded into a flat shape or into a curved shape such as a concave or convex surface depending on the intended use of the laminate. When the resin layer has a curved shape, it is preferable from the viewpoint of strength of the laminate to be bent and molded the glass sheet to match the curved shape of the resin layer, since the shape of the resin layer is restricted by the glass sheet fixed to the curved shape. In addition, when a glass sheet having a thickness of 10 μm to 300 μm is used, the glass sheet deforms to follow the curved surface of the resin layer, so that the laminate can be produced without bending the glass sheet.

[0034] In particular, when the resin layer is formed into a concave curved shape, by making the glass sheet conform to the curved surface of the resin layer formed into a concave shape, compressive stress is formed on the surface of the glass sheet, resulting in good impact absorption properties of the laminate.

[0035] Glass layer The glass layer of the laminate of the present invention is a layer made of a glass sheet. In the present invention, the glass sheet is a sheet containing glass or a sheet made of glass. As described above, the sheet in the present invention includes a sheet, a film, a thin film, a flat plate, etc.

[0036] The glass sheet is not particularly limited and any known glass can be used, but a glass sheet made of silicate glass is preferably used, and more preferably a glass sheet made of at least one type of glass selected from the group consisting of silica glass, borosilicate glass, soda-lime glass, and aluminosilicate glass. The glass sheet may be made of only one type of glass, or may be formed of a mixture of two or more types of glass. Chemically strengthened glass or physically strengthened glass can also be used. A specific example of such a glass sheet is G-leaf manufactured by Nippon Electric Glass Co., Ltd.

[0037] The content of alkali metal oxide contained in the glass sheet is preferably 1.0 mass% or less, more preferably 0.5 mass% or less, and even more preferably 0.3 mass% or less. When the content of alkali metal oxide contained in the glass sheet is 1 mass% or less, it is preferable in terms of weather resistance and light transmittance.

[0038] The thickness of the glass sheet is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less. When the thickness of the glass sheet is 300 μm or less, the laminate becomes lighter and has excellent flexibility. In addition, the thickness is preferably 1 μm or more, more preferably 20 μm or more, from the viewpoint of the strength of the laminate. It is also preferable that the thickness of the glass sheet is smaller than the thickness of the resin layer, whereby the proportion of the glass sheet in the laminate is reduced, and the weight of the laminate can be reduced.

[0039] The density of the glass sheet is 2.60 g / cm to reduce the weight of the laminate. 3 It is preferable that the density is 2.50 g / cm or less. 3 The lower limit of the density is not particularly limited, but is, for example, 1.50 g / cm. 3 or more than 2.00g / cm 3 It can be more than that.

[0040] The surface roughness Ra of the glass sheet is preferably 0.4 nm or less, more preferably 0.3 nm or less. When the surface roughness Ra of the glass sheet is 0.4 nm or less, the light transmittance is good, and the glass sheet can be easily made thin. The lower limit of the surface roughness Ra of the glass sheet is not particularly limited, but can be, for example, 0.01 nm or more, 0.05 nm or more, or 0.1 nm or more. It is preferable that at least one surface of the glass sheet used in the present invention satisfies such a surface roughness Ra, and it is more preferable that both surfaces satisfy such a surface roughness Ra. When the surface that becomes the surface of the laminate of the present invention is composed of a glass sheet, it is preferable that the surface roughness Ra of the surface that becomes the surface satisfies the above range, because the surface of the laminate obtained has excellent flatness and excellent optical properties.

[0041] The water vapor permeability of the glass sheet is 0.5 x 10 -5 g / (m 2 × 24 hr), and the oxygen permeability of the glass sheet is preferably less than 1.0 × 10 -2 cm 3 / (m 2 When the water vapor permeability or oxygen permeability of the glass sheet is less than the above upper limit, the glass sheet can act as a barrier against water vapor or oxygen that has permeated through the resin layer described above and the adhesive layer described below, and therefore when the laminate of the present invention is applied to an electronic device or the like, electronic components provided in the electronic device can be protected from oxygen and water vapor.

[0042] adhesive layer The laminate of the present invention includes an adhesive layer that bonds the resin layer and the glass layer. The material of the adhesive layer is not particularly limited, and an acrylic adhesive or pressure-sensitive adhesive, a urethane adhesive or pressure-sensitive adhesive, a silicon adhesive or pressure-sensitive adhesive, a rubber adhesive or pressure-sensitive adhesive, an ester adhesive or pressure-sensitive adhesive, etc. Also, an adhesive sheet or pressure-sensitive adhesive sheet containing such an adhesive or pressure-sensitive adhesive may be used as the adhesive layer. That is, the adhesive layer may be a double-sided adhesive sheet, a thermoplastic adhesive sheet, a thermally crosslinkable adhesive sheet, an energy-curable liquid adhesive, or the like. For example, an optically transparent adhesive sheet, EVA, TPU, PVB, ionoplast resin, an acrylic thermoplastic adhesive sheet, an ultraviolet-curable adhesive, a heat-curable adhesive, a room temperature-curable adhesive, or the like may be used as the adhesive layer. A specific example of such an adhesive layer is CS9861UAS manufactured by Nitto Denko Corporation.

[0043] The thickness of the adhesive layer is preferably 0.1 to 1000 μm, more preferably 10 to 500 μm. When the thickness of the adhesive layer is 0.1 to 1000 μm, the optical transparency is good, and the adhesive layer can absorb the difference in expansion and contraction caused by the difference in thermal expansion between the resin layer and the glass sheet, and thus the dimensional stability is excellent.

[0044] Laminate The laminate of the present invention includes the resin layer, the glass layer, and an adhesive layer that bonds the resin layer and the glass layer. In other words, the laminate of the present invention includes a resin layer, an adhesive layer, and a glass layer in this order. The laminate of the present invention may have layers other than the resin layer, adhesive layer, and glass layer (for example, layers of wood, paper, glass, metal, prepreg, etc.), or may have the same layers overlapping, so long as the effects of the present invention are not hindered. Examples of layer configurations other than the three-layer structure of resin layer / adhesive layer / glass layer include glass layer / adhesive layer / resin layer / adhesive layer / glass layer, resin layer / adhesive layer / glass layer / adhesive layer / glass layer, resin layer / adhesive layer / resin layer / adhesive layer / glass layer, resin layer / adhesive layer / glass layer / resin layer / adhesive layer / glass layer, resin layer / adhesive layer / glass layer / adhesive layer / glass layer, and the like.

[0045] The oxygen permeability of the laminate of the present invention is 0.1 cm 3 / (m 2 The oxygen permeability of the laminate is preferably less than 0.1 cm 3 / (m 2 When the gas barrier property of the laminate is less than 1 / 24h·atm, the laminate has sufficient gas barrier properties and can prevent the laminate from being deteriorated by oxygen when used in an electronic device (such as a substrate or cover glass for an electronic device, a touch panel, or a planar light-emitting advertising board or guide board).

[0046] The laminate of the present invention has a density of 1.00 g / cm 3 By including a resin layer containing the following resin, the glass sheet has a superior light weight compared to conventional glass sheets and conventional glass resin laminates. In addition, the laminate of the present invention has a glass layer made of a glass sheet, so that the laminate has low water vapor permeability and oxygen permeability, excellent gas barrier properties, and excellent rigidity. Furthermore, when the laminate has a glass layer made of a glass sheet on its surface, the glass sheet exhibits excellent rigidity, so that the laminate has excellent scratch resistance, electrical insulation, chemical stability, surface flatness, chemical resistance, etc.

[0047] When the laminate of the present invention has two or more glass layers, for example, has glass layers on both surfaces, the laminate can have particularly excellent rigidity, weather resistance, gas barrier properties, electrical insulation, chemical stability, surface flatness, chemical resistance, flame retardancy, and the like. Furthermore, when the laminate of the present invention has a glass layer made of a thin glass sheet, for example having a thickness of 300 μm or less, the laminate can have excellent lightweight properties, weather resistance, gas barrier properties, electrical insulation properties, chemical stability, surface flatness, chemical resistance, etc., as well as flexibility. Furthermore, when the resin layer of the laminate of the present invention contains a 4-methyl-1-pentene polymer, the laminate has better optical properties and impact resistance, and even when the resin layer is on the surface of the laminate, the laminate can have excellent heat resistance, chemical resistance, mechanical strength, electrical insulation, and the like.

[0048] <Applications of laminates> The laminate of the present invention can be suitably used for window materials for general buildings and high-rise buildings, platform doors, lighting for roofs, lighting covers, covers and substrates for solar cells, covering materials for agricultural greenhouses, window materials for vehicles such as automobiles and trains, window materials for machine tools, substrates and cover glass for electronic devices, touch panels, planar light-emitting advertising boards and guide boards, partitions, flexible laminates, etc. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto in any way.

[0050] <Measurement and evaluation method> [density] Resin density (g / cm 3 ) was measured in accordance with JIS K7112 (density gradient tube method).

[0051] [Melt flow rate (MFR)] The melt flow rate (MFR) of the resin was measured according to ASTM D1238 under one of the following conditions: 230°C and a load of 3.8 kg, 260°C and a load of 5 kg, or 300°C and a load of 1.2 kg. The conditions under which the measurements were made for each of the Examples and Comparative Examples are shown in the table. The unit of MFR is g / 10 min.

[0052] [Comonomer content] The content (mass%) of the structural units derived from 4-methyl-1-pentene and each comonomer (1-decene, 1-hexadecene, and 1-octadecene) in the 4-methyl-1-pentene copolymer is 13The measurement was performed by C-NMR under the following conditions.

[0053] Measurement conditions Measurement equipment: Nuclear magnetic resonance equipment (ECP500 type, manufactured by JEOL Ltd.) Observation kernel: 13 C(125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds Number of times: 10,000 or more Solvent: orthodichlorobenzene / deuterated benzene (volume ratio: 80 / 20) mixed solvent Sample concentration: 55mg / 0.6mL Measurement temperature: 120℃ Chemical shift reference value: 27.50 ppm

[0054] [Oxygen permeability] The oxygen permeability of the laminate was measured in accordance with JIS K7126-1 using a differential pressure gas permeability measuring device (manufactured by Toyo Seiki Seisakusho) at a test temperature of 23°C and a test humidity of 0% RH over a measurement area of ​​5 cm 2 The measurement area of ​​the laminate was adjusted by preparing two Modern Kotrol adhesive aluminum masks with a 25 mm diameter hole in the center, and laminating the gas permeable film to be measured between the two masks. In detail, the laminate was positioned so that the hole in the center was overlapped by the two masks.

[0055] [Gakushin abrasion test (scratch resistance)] A Gakushin abrasion tester (manufactured by Toyo Seiki Co., Ltd.) and a 470g abrasion indenter made of 45R SUS with the tip covered with steel wool φ16mm were used. The sample was abraded using this abrasion indenter under the following conditions: 20 reciprocations at 23°C, reciprocation speed of 30 reciprocations / min, stroke of 30mm. The gloss retention (Δgloss) before and after abrasion was calculated as follows. The higher this value, the better the scratch resistance. Gloss retention rate = 100 x gloss after wear / gloss before wear

[0056] [Example 1] A rectangular glass sheet (G-leaf, manufactured by Nippon Electric Glass Co., Ltd.) measuring 100 mm in length, 100 mm in width, and 50 μm in thickness was prepared and used as is in an unpolished state. The physical properties of this glass sheet (G-leaf) are as follows: surface roughness Ra 0.2 nm, content of alkali metal oxides contained in the glass sheet 0.1 mass % or less, density 2.46 g / cm 3 , water vapor permeability is 0.5×10 -5 g / (m 2 ×24hr), oxygen permeability is less than 1.0×10 -2 cm 3 / (m 2 ·24hr·atm). The resin layer was made of 4-methyl-1-pentene-1-decene copolymer (decene content = 3.0 mass%, MFR: 26 g / 10 min, density: 0.83 g / cm 3 ) was used to prepare a rectangular transparent injection piece measuring 120 mm in length, 120 mm in width, and 2.0 mm in thickness. An acrylic adhesive sheet (CS9861UAS, made by Nitto Denko Corporation, thickness 25μm) was laminated as an adhesive layer on one side of the resin layer, and then a glass sheet was laminated on the adhesive layer to produce a glass resin laminate with a three-layer structure of resin layer / adhesive layer / glass sheet, and the scratch resistance and oxygen permeability were evaluated. The results are shown in Table 1.

[0057] [Example 2] The resin layer was made of 4-methyl-1-pentene-1-hexadecene-1-octadecene copolymer (1-hexadecene-1-octadecene content = 6.5 mass%, MFR: 100 g / 10 min, density: 0.83 g / cm 3 ) was used, a laminate was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0058] [Example 3] The resin layer was made of 4-methyl-1-pentene-1-decene copolymer (decene content = 3.4 mass%, MFR: 110 g / 10 min, density: 0.83 g / cm 3) was used, a laminate was produced and evaluated in the same manner as in Examples 1 and 2. The results are shown in Table 1.

[0059] [Comparative Example 1] A rectangular glass thin film (G-leaf manufactured by Nippon Electric Glass Co., Ltd., the same as that used in Example 1) measuring 100 mm in length, 100 mm in width, and 50 μm in thickness was prepared and used as it was in an unpolished state. A 4-methyl-1-pentene-1-decene copolymer (decene content = 3.0 mass%, MFR: 26 g / 10 min, density: 0.83 g / cm) was used as the resin layer. 3 ) was used to prepare a rectangular transparent injection piece measuring 120 mm in length, 120 mm in width, and 2.0 mm in thickness. A glass sheet was laminated on one side of the resin layer to produce a glass resin laminate with a two-layer structure of resin layer / glass sheet, and the scratch resistance and oxygen permeability were evaluated. The results are shown in Table 1.

[0060] [Comparative Example 2] The resin layer was made of 4-methyl-1-pentene-1-hexadecene-1-octadecene copolymer (1-hexadecene-1-octadecene content = 6.5 mass%, MFR: 100 g / 10 min, density: 0.83 g / cm 3 ) was used, a laminate was produced and evaluated in the same manner as in Comparative Example 1. The results are shown in Table 1.

[0061] [Comparative Example 3] The resin layer was made of 4-methyl-1-pentene-1-decene copolymer (decene content = 3.4 mass%, MFR: 110 g / 10 min, density: 0.83 g / cm 3 ) was used, a laminate was produced and evaluated in the same manner as in Comparative Examples 1 and 2. The results are shown in Table 1.

[0062] [Comparative Example 4] The resin layer was made of polycarbonate resin (SD POLYCA TM 301-10, density: 1.20g / cm 3 ) was used, a laminate was produced and evaluated in the same manner as in Examples 1 to 3. The results are shown in Table 1.

[0063] [Comparative Example 5] The resin layer was made of acrylic resin (Acrypet MD001, manufactured by Mitsubishi Chemical Corporation, density: 1.18 g / cm 3 ) was used, a laminate was produced and evaluated in the same manner as in Examples 1 to 3. The results are shown in Table 1.

[0064] [Table 1]

[0065] In Examples 1 to 3, the laminated glass sheets provided excellent scratch resistance, low oxygen permeability, and were lightweight. On the other hand, in Comparative Examples 1 to 3, the laminated glass sheets provided poor scratch resistance and high oxygen permeability. In Comparative Examples 4 and 5, the laminated glass sheets provided excellent scratch resistance and low oxygen permeability, but the resin used in the Comparative Examples 4 and 5 had a higher density than the resin used in Examples 1 to 3, and therefore had a larger mass.

Claims

1. Density is 1.00 g / cm 3 A resin layer containing the following resin: A glass layer made of a glass sheet; an adhesive layer that bonds the resin layer and the glass layer; A laminate comprising:

2. Oxygen permeability is 0.1 cm 3 / (m 2 24 hr atm).

3. 2. The laminate according to claim 1, wherein the resin comprises at least one selected from the group consisting of a homopolymer of 4-methyl-1-pentene and a copolymer of 4-methyl-1-pentene with ethylene or an α-olefin (excluding 4-methyl-1-pentene).

4. The resin comprises a copolymer of 4-methyl-1-pentene and an α-olefin (excluding 4-methyl-1-pentene), The laminate according to claim 3, wherein the α-olefin is an α-olefin having 3 to 20 carbon atoms.

5. the resin comprises a copolymer of 4-methyl-1-pentene and ethylene or an α-olefin (excluding 4-methyl-1-pentene); The laminate according to claim 3, wherein the content of structural units derived from 4-methyl-1-pentene in the resin is 70.0 to 99.0% by mass, and the content of structural units derived from ethylene or the content of structural units derived from α-olefin in the resin is 1.0 to 30.0% by mass (wherein the total of the content of structural units derived from 4-methyl-1-pentene and the content of structural units derived from ethylene or the content of structural units derived from α-olefin is 100.0% by mass).

6. 2. The laminate according to claim 1, wherein the resin has an MFR (260° C., 5 kg) of 0.1 to 500 g / 10 min.

7. The laminate according to claim 1 , wherein the glass sheet has a thickness of 300 μm or less.

8. The laminate according to claim 1 , wherein at least one surface of the glass sheet has a surface roughness Ra of 0.4 nm or less.

9. An electronic device comprising the laminate according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Glass resin laminate

    JP2014012373A